Learning Planning for Islamic Religious Education and Character Based on Independent Learning at the Saleh Islamic Elementary Education Institute, Malang City - Muhammad Ilham Akbar; Triyo Supriyatno; Mohammad Asrori (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract SD Anak Saleh as an Islamic basic education institution has responded quickly to the concept of independent learning through Pancak Character as an educational philosophy. This is what makes the institution innovate in learning, especially the aspects of planning the learning of Islamic religious education and character in achieving the goal of learning freedom. The research method in this research is field research with a descriptive qualitative approach and type of case study research. The results of this study indicate that the planning of PAI learning and character based on independent learning is carried out in two steps, namely forming a special PAI subject team and the preparation of learning tools based on institutional independence. Keyword : Learning Planning, Islamic Religious Education and Character, Free Learning